A Communicative Language Teaching Approach in Technology Enhanced English Classrooms: A Linguistic Perspective - Hutauruk, Desi Ramadali; Daulay, Sholihatul Hamidah; Dalimunte, Muhammad (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
This research aims to gain insights into teachers' perceptions and practices regarding CLT principles and their alignment with linguistic theories of language learning. A qualitative approach was used by involving 10 English teachers from different secondary schools in North Sumatra using purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis and analyzed through inductively using thematic analysis. The findings reveal a strong emphasis on authentic language use, development of communicative competence, student-centered and interactive approaches, and integration of digital technology to facilitate real-time communication and collaborative language learning experiences. Therefore CLT and linguistic perspective in the language classroom and potential role of technology in enhancing effective communicative language teaching.